2022
DOI: 10.3390/nu14061280
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of a Novel Form of Biotin on Propionic Acid-Induced Autistic Features in Rats

Abstract: Magnesium biotinate (MgB) is a novel biotin complex with superior absorption and anti-inflammatory effects in the brain than D-Biotin. This study aimed to investigate the impact of different doses of MgB on social behavior deficits, learning and memory alteration, and inflammatory markers in propionic acid (PPA)-exposed rats. In this case, 35 Wistar rats (3 weeks old) were distributed into five groups: 1, Control; 2, PPA treated group; 3, PPA+MgBI (10 mg, HED); 4, PPA+MgBII (100 mg, HED); 5, PPA+MgBIII (500 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 101 publications
2
6
0
Order By: Relevance
“…This is due to the antioxidant neuroprotective effect of both Co-Q10 and LCo-Q10, and increase brain mitochondrial concentrations in animal studies and reduces markers of oxidative damage in the cerebral cortex and hippocampus. The present findings is in agreement with the study reported by [3] that neuroglial activation together with a decrease in the number of cerebellar Purkinje cells and an increase in certain cytokines were investigated in ASD brain tissues. As reported previously, both humans and animals with ASD display altered structures and functions in various brain areas, such as the hippocampus [39] and the cortex [40] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is due to the antioxidant neuroprotective effect of both Co-Q10 and LCo-Q10, and increase brain mitochondrial concentrations in animal studies and reduces markers of oxidative damage in the cerebral cortex and hippocampus. The present findings is in agreement with the study reported by [3] that neuroglial activation together with a decrease in the number of cerebellar Purkinje cells and an increase in certain cytokines were investigated in ASD brain tissues. As reported previously, both humans and animals with ASD display altered structures and functions in various brain areas, such as the hippocampus [39] and the cortex [40] .…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, PPA can alter genes, related to autism pathogenesis, that controls neuroplasticity, oxidative stress, neurotransmitters, neurodevelopment, mitochondrial function and inflammation [2] . PPA can induce brain and behavioral disturbance in animal model identical to those of autistic human beings, via fluctuating brain FA metabolism [3] .…”
Section: Introductionmentioning
confidence: 99%
“…PPA administration in rats caused pathophysiological and clinical features similar to those seen in ASD patients (Ali et al, 2022;Khera et al, 2022;Sahin et al, 2022). Therefore, the PPA model serves as valid animal model to study the underlying neurobiology of ASD.…”
Section: Introductionmentioning
confidence: 91%
“…Magnesium biotinate, a novel biotin complex with superior absorption, has been effective in decreasing the expression of neurotoxicity-related cytokines, improving the brain and serum magnesium, biotin, serotonin, and dopamine concentrations, and ameliorating dysfunctions in social behavior, learning, and memory in propionic acid-exposed rats with ASD behaviors [ 100 ]. A study conducted in the USA reported that biotin levels of ASD were 20% lower compared to neurotypical controls, and nearly 7% of those with ASD had biotin levels below the reference range [ 27 ].…”
Section: Vitaminsmentioning
confidence: 99%